Computer evidence: issues and challenges in the present and in the future - Mohamed, Duryana (2011)
Computer evidence is sometimes known as digital evidence. It is also categorized as electronic evidence. In Malaysia, computer evidence is described as computer printout or output and admissible in the court of law. The admissibility of computer printout is mentioned in sections 90A, 90B and 90C of the Evidence Act 1950. The most common issues on computer printout are, ‘whether the printout is produced by a computer in the course of its ordinary use' and ‘whether certificate is needed or not needed to prove the authenticity of the computer printout'. These issues are raised in cases where the computer printout is produced as evidence. However, the admissibility of computer printout may be challenged when the evidence is available in other forms or medium. In the past, paper is produced as documentary evidence so as in the present cases. But in future, there may be situation where lawyers or prosecutors may not be able to satisfy the court in proving the reliability and admissibility of computer evidence. Things will be more complicated if the case involve cyber-related cases and various jurisdictions. Consequently, the suspect may escape liability due to technical defect or mistakes. This paper aims to discuss the position of computer evidence and its application in the Malaysian courts. Decisions on computer evidence from other courts of similar jurisdiction will also be referred to as to identify issues and the possible challenges that may arise in the future.